Promosi Soft Sell Prodi D4 Animasi Politeknik Negeri Padang Menggunakan Desain Karakter Sebagai Intellektual Property - Hendra Rotama; Sumema; Taufik Gusman; Ardian Firosha; Sofia Yose (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
An effective strategy is required to ensure that the identity of a newly established academic program stands out and appears distinct from its competitors. One approach that can be used in soft selling promotion is the development of intellectual property (IP) in the form of character design. Character design not only serves as a visual element, but also acts as a medium to convey messages that represent the identity and uniqueness of the new academic program. The use of IP in the form of character design, implemented through a soft selling strategy, allows for the persuasive delivery of information without directly pressuring the target audience.